(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
In the following essay, I consider if and how VR’s uncanny ability to create an illusion of presence and generate a sense of body ownership might be used to go beyond our anthropocentric perspective, towards non-human experiences. By adventuring outside the domain of human experience, my goal is to address the affordances and limitations of VR’s illusionistic potential. Knowing full well that certain economic pressures preclude artists from pursuing the kinds of provocations I describe in this essay, I nevertheless invite readers to follow along as I explore alternative potentialities of contemporary VR. Specifically, I approach VR here in the hopes of finding ways of engaging with different bodies, spaces, and realities, even if illusorily.